Iterative MMSE equalization and CFO compensation for the uplink SC‐FDMA transmission. (7th January 2016) - Selvaraj, K.; Ganeshkumar, P.; Anandaraj, M.
Summary: Single‐carrier frequency division multiple access is greatly sensitive to carrier frequency offset (CFO) between transceivers. This leads to the destruction of orthogonality among subcarriers, which in turn leads to inter‐carrier interference and multiple access interference between different users. Minimum mean square error (MMSE) equalizer that uses an inverse operation on an interference matrix with a dimension equal to the number of subcarriers is normally used to invalidate CFO effects. Hence, the terminal processing complexity is very high. The proposed conjugate gradient method attempts to mitigate the higher computational complexity by iteratively evaluating the MMSE solution without direct matrix inverse operation. To further mitigate the multiple access interference, MMSE combined with parallel interference cancellation is also implemented. The analysis of the proposed method shows better performance and fast convergence in single‐carrier frequency division multiple access systems. The maximum iteration number to formulate an accurate solution is almost equal to the number of active users in the uplink access. Simulation results bring out the effectiveness of the present method compared with the existing CFO compensation schemes in terms of computational complication and system performance with large frequency offsets. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work proposes iterative minimum mean square error (MMSE) equalization‐based carrier frequency offset (CFO) compensation for single‐carrier frequency division multiple access (SC‐FDMA) uplink system. SC‐FDMA is highly sensitive to CFO. To mitigate the CFO effects, MMSE equalizer is used (with an inverse operation in interference matrix of size equal to the number of subcarriers). But this increases the computational complexity. Therefore, to reduce the computational complexity, conjugate gradient method that finds the MMSE solution by iteration technique is employed in this paper. This method shows better performance and fast convergence in SC‐FDMA systems. Obviously, the proposed conjugate gradient algorithm‐based MMSE scheme achieves an excellent performance improvement in terms of processing delay, as well as complexity. From the simulation result, the computational complexity of MMSE equalizer is reduced by applying the conjugate gradient method to compensate the CFO.